A case of acute pancreatitis with normal serum lipase (Bangladesh Medical Journal, 2016)
Patients with acute pancreatitis typically present with epigastric pain. In such patients, demonstration of elevated pancreatic enzymes and swollen pancreas by radiological investigations are sufficient to confirm the diagnosis. Here we present case history of a middle aged man who had epigastric pain, fever and swollen pancreas but enzyme levels were normal. He responded to conventional conservative treatment.Bangladesh Med J. 2014 Sep; 43 (3): 162-164